The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.3354/meps281155
|View full text |Cite
|
Sign up to set email alerts
|

Predation by the mysid shrimps Mysis mixta and M. relicta on benthic eggs of Bosmina longispina maritima (Cladocera) in the northern Baltic Sea

Abstract: The abundance of Bosmina longispina maritima (Cladocera), the most common water flea in the Baltic Sea, shows considerable interannual fluctuations.The number of Bosmina resting eggs (ephippia) in the sediment also fluctuates from year to year. Biotic as well as abiotic factors have been suggested to contribute to these fluctuations, but the impact of benthic predation by pelagic mysids has not yet been considered. The objective of this study was to investigate the effect of benthic predation and bioturbation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…For example, omnivorous crayfish display trophic positions close to those of predatory fish –which is higher than would be expected from gut content analysis alone [73]. Mysids feeding on meiofauna, zooplankton resting eggs and small amphipods [74], [75] could have contributed to this apparent similarity in δ 13 C between the groups at station S1. The more carnivorous nature of pelagic mysids [13] is further supported by substantially stronger δ 15 N, δ 13 C-correlations as compared to benthic individuals that appear to have broader, more omnivorous diets.…”
Section: Discussionmentioning
confidence: 91%
“…For example, omnivorous crayfish display trophic positions close to those of predatory fish –which is higher than would be expected from gut content analysis alone [73]. Mysids feeding on meiofauna, zooplankton resting eggs and small amphipods [74], [75] could have contributed to this apparent similarity in δ 13 C between the groups at station S1. The more carnivorous nature of pelagic mysids [13] is further supported by substantially stronger δ 15 N, δ 13 C-correlations as compared to benthic individuals that appear to have broader, more omnivorous diets.…”
Section: Discussionmentioning
confidence: 91%
“…-1 in only 12 h (Viitasalo & Viitasalo 2004). However, except for the statistically insignificant additional decrease in ephippia (< 3 d -1 ) in the treatment combining Monoporeia with mysids, no such effect was observed, i.e.…”
Section: Epibenthic Predation By Mysidsmentioning
confidence: 99%
“…According to Viitasalo & Viitasalo (2004) Mysis mixta is unable to feed on ephippia buried in sediment; hence, it was suggested that bioturbation by macrofauna may essentially affect the predation by epibenthic mysids on their non-motile benthic prey. Consequently, one aim of this study was to test whether macrofauna could, by means of particle mixing, redistribute ephippia, buried under a sediment layer of 0.5 to 1 cm, within the reach of the mysids. )…”
Section: Epibenthic Predation By Mysidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly selective interferometric filters are formed by tens of these layers [4]. Less selective but more feasible filters can be got with a more modest number of layers (as few as three) following a Fabry-Perot scheme [5]. In silicon processing environments, silicon dioxide and polysilicon layers can play the role of low and high index materials.…”
Section: Infrared Filter and Detectormentioning
confidence: 99%